Active travel and the built environment: A theoretical model and multidimensional evidence. (November 2021) - Wu, Jiayu; Wang, Binhui; Wang, Rui; Ta, Na; Chai, Yanwei
Highlights: An active travel demand model incorporates the intrinsic benefits of travel. A simultaneous analysis of active travel frequency, distance and duration. Use a natural experiment of randomized residential location. Measure built environmental characteristics at alternative spatial scales. Travel behavior is affected by modal characteristics and intermodal substitution. Abstract: This study proposes a demand model incorporating active travel's intrinsic benefits and analyzes the built environment's impact on the active travel behavior of commuters in a subarea of Beijing. The combined use of GPS trajectories and travel diary enables simultaneous analyses of multiple travel behavior metrics measuring both physical activity and mode choice. China's unique institutional context provides a natural experiment of randomized residential location. Empirical analyses show that the active travel impact of the built environment are complex depending on location and active travel metric, and are equally important as those of individual and household attributes for active travel duration and distance. Dense and diverse employment centers and open space in residential areas seem to promote active travel in commute. Different policy goals related to active travel, such as public health and congestion and emissions mitigation, might not be achieved simultaneously by a specific built environmental intervention.